Depiction of Vishnu seated on a pedestal - Temples of India Project Team (Jio Institute, 2024)
On the western bhadra (central offset) of the garbhagriha (sanctum sanctorum) of the Hazareshwar Temple, there is a depiction of Vishnu seated on a pedestal. Vishnu is portrayed with four arms, holding a gada (mace) and a chakra (discus) in his upper hands, and a shankha (conch shell) in his lower left hand, while his lower right hand is in the Varada hasta (hand gesture of conferring a boon) posture. He is adorned with elaborate accessories, including a kirita mukuta (conical cylinder-shaped crown generally attributed to Vishnu iconography), large earrings, a broad necklace, a chest band, a heavy girdle, bangles, and anklets, enhancing his divine appearance.